Blessed Vasyl Velychkovsky's ancestral relationship with venerable Paisius Velychkovsky and Chernihivshchyna - Welyczkowsky, (Welleck) George (Сiверянський літопис, 2021)
Purpose: To determine whether two prominent Ukrainian figures with identical
surnames and with ancestors who lived in the Chernihiv region were genetically
related. Discoveries about the ancestries of Venerable Paisius Velychkovsky (1722–
1794) and Blessed Vasyl Velychkovsky (1903–1973) have advanced and curated data
leads to new hypothetical conclusions about their paternal genealogical connection.
Methodology: Findings and conclusions are presented using an anthropological and
chronological approach relying on published works and family archives. Scientific
Novelty: For the first time a documented attempt to jointly explore and profile the
collective origins of Ven. Paisius Velychkovsky and Bl. Vasyl Velychkovsky is made to
determine whether they are genealogically related. Conclusions: Two historically
prominent Ukrainian figures born almost 200 years apart shared the same paternal
surname. Their significance was elevated when Ven. Paisius Velychkovsky was
canonized by the Orthodox church in June 1988, more than a century after hisrelics
were uncovered and found to be incorrupt. Similarly, Bl. Vasyl Velychkovsky was
declared a Christian martyr for his faith in 2001, and thirty years after his death, his
body with the exception of his toes was also found to be incorrupt. Ven. Paisius was
the last living member of his immediate family, thus his immediate family line became
extinct with his passing, while Bl. Vasyl was celibate but had two sisters whose
families exist to present day. While their families’ descendants are limited, a focus on
their paternal ancestors reveals that they both once lived in the Chernihiv region of
Ukraine and that their common surname and its derivations existed in Lithuania prior
to the earliest known occurrences in Ukraine. Surnames of related families to the
Velychkovsky family in the Chernihiv region also existed in Lithuania. Heraldry and in
particularcoats of arm associated with the Velychkovsky surname establish yet
another link to a hypothetical Velychkovsky ancestry dating back to Lithuanian King
Gediminas in the XIV century. Limited but circumstantial evidence suggests they are
both related by paternal descent from a common ancestral nest in Lithuania. The
possibility of scientifically answering the question of whether they have a genealogical
connection using DNA remains a distinct and extant possibility. Праця присвячена двом значним та видатним українським діячам, які мають одне і те саме прізвище: преподобному Паїсію Величковському (1722–1794) та блаженному Василю Величковському (1903–1973). Прп. Паїсій визнаний Православною Церквою святим. Він був канонізований у 1988 році з нагоди тисячоліття Хрещення Київської Русі, попередниці України. Бл. Василя визнано мучеником Української Греко-Католицької Церкви та блаженним у 2001 році Папою
Римським Іваном-Павлом ІІ. В автобіографії прп. Паїсій писав, що він був 11-м
із 12-ти братів і сестер і останнім живим членом його найближчої родини. Родинна лінія прп. Паїсія вимерла з його смертю. Бл. Василь все життя був безшлюбним, але мав двох сестер із сім’ями, які живі до теперішнього дня. Нещодавно з’явились знахідки, які свідчать про те, що предки прп. Паїсія та бл. Василя колись мешкали на Чернігівщині в Україні. Окрім того, прізвище «Величковський» простежується за родовим походженням у Литві, починаючи з родин XIV ст. Дізнання, чи прп. Паїсій та його родина мають спільних предків з
бл. Василем, не лише вирішить постійне питання, на яке у самого бл. Василя
остаточної відповіді не було, але також може стати ще однією позитивною
силою християнської єдності між Українською Греко-Католицькою Церквою
та Православною Церквою України. У випадку, якщо вони пов’язані між собою,
дві Церкви, які стали правонаступниками хрещення України в 988 році, могли б
відзначати родинну лінію, яка колись жила на Чернігівщині та яка призвела до
канонізації святого в Українській Православній Церкві та блаженного мученика
в Українській Католицькій Церкві. Дотепер не було серйозно досліджено, як пов’язані ці дві впливові, видатні та святі особи.